INSURANCE PROTECTION FOR FISHERMEN - Marnia Rani (Program Studi Ilmu Hukum Universitas Maritim Raja Ali Haji, 2016)
Indonesia is an archipelagic state which surrounded by the sea. Indonesia's marine area is 5.8 million square kilometers comprising the territorial area of 3.2 million square kilometers and the Indonesian Exclusive Economic Zone (ZEEI) of 2.7 million square kilometers. In addition, there are 17,504 islands in Indonesia with 95 181 square kilometer coastline. With that area, it should be utilized to the overall prosperity of the people in order to improve standard of living. Especially for fishermen who depend for their livelihood on fishing in the sea. The majority of fishing boats are not equipped for serious medical emergencies, and most boats are usually Several hundred miles away from the nearest medical facility. Many events can occur during deep-sea fishing, such as changing weather conditions, ship collisions, which can lead to lost profits or lost their lifes, can be happen to fishermen. For that reason, they need mechanism to overcome the risk of losses With insurance mechanism, they can minimize the loss of profit or their life that would cause the families of fishermen to lose income for their family's livelihood. Recently, The House of Representatives passing Law Number 7 of 2016 Regarding The Protection and Empowerment of Fishermen, Fish Farmers and Salt Farmers. The Law stipulates that both central and local governments must protect people working in these sectors from occupational risks, including work accidents and equipment damage. Also, Maritime and Fisheries Minister, Susi Pudjiastuti, said Maritime and Fisheries Ministry was seriously realizing the fishermen insurance. The fishermen insurance will cover life and business insurances. Therefore, fishermen will have guarantee over the risks of fishing, aquaculture, and fish-salting businesses. Keywords: Insurance, Fishermen Indonesia adalah negara kepulauan yang dikelilingi oleh laut. Kawasan laut Indonesia adalah 5,8 juta kilometer persegi yang terdiri dari wilayah teritorial 3,2 juta kilometer persegi dan Zona Ekonomi Eksklusif Indonesia (ZEEI) 2,7 juta kilometer persegi. Selain itu, ada 17.504 pulau di Indonesia dengan garis pantai 95.181 kilometer persegi. Dengan wilayah seluas itu, harus dapat dimanfaatkan secara keseluruhan untuk kemakmuran rakyat agar dapat meningkatkan taraf hidup yang lebih baik. Khususnya bagi nelayan yang menggantungkan hidupnya dari mencari ikan di laut. Kebanyakan kapal nelayan dalam mencari ikan, jauh dari tempat medis terdekat. Peristiwa yang tidak diinginkan, seperti peristiwa alam badai, tabrakan kapal yang mengakibatkan kehilangan keuntungan atau kehilangan nyawa, sangat mungkin terjadi bagi nelayan saat melaut. Untuk itu diperlukan suatu mekanisme peralihan risiko kerugian yang dialami nelayan ketika menangkap ikan di laut. Dengan mekanisme peralihan risiko kerugian, nelayan dapat meminimalisir kehilangan keuntungan ataupun kerugian atas hasil tangkap ikan maupun terhadap kehilangan nyawa yang akan membuat keluarga nelayan menjadi kehilangan penghasilan bagi nafkah keluarganya. Baru-baru ini, Dewan Perwakilan Rakyat mengesahkan Undang-Undang Nomor 7 Tahun 2016 Tentang Perlindungan dan Pemberdayaan Nelayan, Petani Tani dan Petani Garam. Undang-undang tersebut menetapkan bahwa pemerintah pusat dan daerah harus melindungi orang-orang yang bekerja di sektor laut dari risiko pekerjaan, termasuk kecelakaan kerja, sakit, dan kerusakan peralatan untuk melaut. Selain itu, Menteri Kelautan dan Perikanan Susi Pudjiastuti mengatakan, Kementerian Kelautan dan Perikanan (KKP) serius mewujudkan asuransi nelayan. Asuransi nelayan akan mencakup asuransi jiwa dan bisnis. Oleh karena itu, nelayan akan memiliki jaminan atas risiko usaha penangkapan ikan, akuakultur, dan penggalangan ikan. Kata kunci: Asuransi, Nelayan